THE SURROGATE MOTHERHOOD AGREEMENT: A PROPOSED STANDARD FORM CONTRACT FOR QUEBEC - Kasirer, Nicholas (Revue de droit de l'Université de Sherbrooke, 1985)
The author proposes a standard form contract for Quebec parties who seek to enter into a surrogate motherhood arrangement. After carefully considering the contract from the point of view of the Quebec notion of public order and good morals, the author argues that the parties are free to enter into a surrogate motherhood contract when the arrangement represents a treatment of infertility which is in the best interest of the surrogate mother and the prospective child. Each clause of the contract is explained and commented on fully, with particular attention to the questions of the validity and the enforceability of the arrangement under Quebec law. The author contends that circumstances do exist in which a well drafted and well thought out agreement will not offend the public interest, and he is confident that the Quebec law of contract can regulate this unique commercial transaction and the family relationships it creates.